Communication regarding the geology and vertebrate palaeontology of the Adamantina formation (Bauru group, Upper Cretaceous) in Campina Verde, Minas Gerais State, Brazil - A. Candeiro Carlos Roberto; Carvalho Adelino; Silva Limonta Filipi; Sullivan de Jesus Alves Diego; Rangel Caio César; Ferreira de Oliveira Emerson (Earth Sciences Research Journal)
Several geological events occurred onthe surface of the earth with the division of the megacontinent Gondwana, including volcanic activity involving extensive lava flows, thus locally and regionally altering the surface's geology. Lava flows in the Serra Geral formation predominantly consist of volcanic lava fissure-derived basalt. Sedimentation upon extrusive igneous rocks occurred after this volcanic event, leading to the deposition of sediments from three formations (Adamantina, Uberaba, and Marília) collectively comprising the upper Cretaceous Bauru group, beginning about 83 million years ago. This was a period when large animals inhabited the planet, including the study area; the Adamantina formation is the largest and oldest. The city of Campina Verde is located there and is where most studies were carried out; the region is known as fossil field.